Marshall Characteristics of Asphalt Concrete – Wearing Course (AC-WC) With Substitution of Silica Sand as Fine Aggregate - Mukhlis Mukhlis; Lusyana Lusyana; Enita Suardi; Denisa Rahma Sukri; Alyza Sazama (JURUSAN TEKNIK SIPIL, 2023)
The growth of traffic loads in Indonesia has increased significantly, but road infrastructure has developed disproportionately. Excessive loads can damage roads because they exceed the planned capacity. Aggregates, especially fine aggregates, play an important role in inclined flexible pavement layers, namely in AC-WC layers. AC-WC aims to provide smoothness, safety and comfort for road users, as well as protect the underlying layers from damage due to traffic loads such as collapse, grooves and bleeding. The use of silica sand is an alternative used to improve the quality of AC-WC layers. This research aims to obtain the Optimum Asphalt Content (KAO) value. The KAO value using the Marshall method on the AC-WC mixture was 5.99% for 0% silica sand, 5.88% for 25% silica sand, 5.845% for 50% silica sand, 5.835% for 75% silica sand, 5.810% in the 100% silica sand variation. Thus the more percentage of silica sand added as a fine aggregate substitution in the AC-WC mixture, the lower the KAO value obtained.